Alteration of Differentiation Potentials by Modulating GATA Transcription Factors in Murine Embryonic Stem Cells - Callinice D. Capo-chichi; Jennifer L. Smedberg; Malgorzata Rula; Emmanuelle Nicolas; Anthony T. Yeung; Richard F. Adamo; Andrey Frolov; Andrew K. Godwin; Xiang-Xi Xu (Hindawi Limited, 2010)
Background. Mouse embryonic stem (ES) cells can be differentiated in vitro by aggregation and/or retinoic acid (RA) treatment. The principal differentiation lineage in vitro is extraembryonic primitive endoderm. Dab2, Laminin, GATA4, GATA5, and GATA6 are expressed in embryonic primitive endoderm and play critical roles in its lineage commitment. Results. We found that in the absence of GATA4 or GATA5, RA-induced primitive endoderm differentiation of ES cells was reduced. GATA4 (−/−) ES cells express higher level of GATA5, GATA6, and hepatocyte nuclear factor 4 alpha marker of visceral endoderm lineage. GATA5 (−/−) ES cells express higher level of alpha fetoprotein marker of early liver development. GATA6 (−/−) ES cells express higher level of GATA5 as well as mesoderm and cardiomyocyte markers which are collagen III alpha-1 and tropomyosin1 alpha. Thus, deletion of GATA6 precluded endoderm differentiation but promoted mesoderm lineages. Conclusions. GATA4, GATA5, and GATA6 each convey a unique gene expression pattern and influences ES cell differentiation. We showed that ES cells can be directed to avoid differentiating into primitive endoderm and to adopt unique lineages in vitro by modulating GATA factors. The finding offers a potential approach to produce desirable cell types from ES cells, useful for regenerative cell therapy.